2022
DOI: 10.3389/fcvm.2022.855682
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Specific Biomarkers Indicate Cardiac Adaptive and Anti-inflammatory Response of Repeated Recreational SCUBA Diving

Abstract: ObjectiveRecreational SCUBA (rSCUBA) diving has become a highly popular and widespread sport. Yet, information on molecular events underlying (patho)physiological events that follow exposure to the specific environmental conditions (hyperbaric conditions, coldness, immersion, and elevated breathing pressure), in which rSCUBA diving is performed, remain largely unknown. Our previous study suggested that repeated rSCUBA diving triggers an adaptive response of cardiovascular and immune system. To elucidate furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 132 publications
(177 reference statements)
0
2
0
Order By: Relevance
“…Dumić et al [ 147 ] reported that regular recreational SCUBA diving promotes an anti-inflammatory status, thus contributing to cardioprotection and conferring multiple health benefits. Divers who performed five dives, one per week, at a depth of 20–30 m that lasted 30 min, manifested IgG and TPP N-glycosylation alterations toward anti-inflammatory status over the whole study period with an increase in monogalyctosylated and core-fucosylated IgG N-glycans and a decrease in galactosylated TPP N-glycans.…”
Section: The Oxy-inflammation Mechanism In Underwater Activitymentioning
confidence: 99%
“…Dumić et al [ 147 ] reported that regular recreational SCUBA diving promotes an anti-inflammatory status, thus contributing to cardioprotection and conferring multiple health benefits. Divers who performed five dives, one per week, at a depth of 20–30 m that lasted 30 min, manifested IgG and TPP N-glycosylation alterations toward anti-inflammatory status over the whole study period with an increase in monogalyctosylated and core-fucosylated IgG N-glycans and a decrease in galactosylated TPP N-glycans.…”
Section: The Oxy-inflammation Mechanism In Underwater Activitymentioning
confidence: 99%
“…To contribute to the understanding of adaptive mechanisms triggered by rSCUBA diving practiced once a week and get a more comprehensive insight into molecular events during and after the dive as well as its cumulative effects, we undertook a comprehensive longitudinal intervention study, which showed that rSCUBA diving repeated weekly triggers an adaptive response in cardiovascular (CV) and immune systems, muscles, and haematopoiesis ( 25 28 ). In this study, we aimed to explore neurohormonal events during and after rSCUBA diving, as well as, the cumulative effect of five dives practiced once a week, by measuring the serum concentration of ACTH, cortisol, TSH, free thyroxine (fT4), prolactin, total testosterone, GH, and insulin-like growth factor 1 (IGF-1), a primary mediator of the GH effects, whose main source is the liver but active muscles as well ( 29 ).…”
Section: Introductionmentioning
confidence: 99%